Ancient DNA and morphometric analysis reveal extinction and replacement of New Zealand's unique black swans. Issue 1859 (26th July 2017) - Rawlence, Nicolas J.; Kardamaki, Afroditi; Easton, Luke J.; Tennyson, Alan J. D.; Scofield, R. Paul; Waters, Jonathan M.
Abstract : Prehistoric human impacts on megafaunal populations have dramatically reshaped ecosystems worldwide. However, the effects of human exploitation on smaller species, such as anatids (ducks, geese, and swans) are less clear. In this study we apply ancient DNA and osteological approaches to reassess the history of Australasia's iconic black swans ( Cygnus atratus ) including the palaeo-behaviour of prehistoric populations. Our study shows that at the time of human colonization, New Zealand housed a genetically, morphologically, and potentially ecologically distinct swan lineage ( C. sumnerensis, Poūwa), divergent from modern (Australian) C. atratus . Morphological analyses indicate C. sumnerensis exhibited classic signs of the 'island rule' effect, being larger, and likely flight-reduced compared to C. atratus . Our research reveals sudden extinction and replacement events within this anatid species complex, coinciding with recent human colonization of New Zealand. This research highlights the role of anthropogenic processes in rapidly reshaping island ecosystems and raises new questions for avian conservation, ecosystem re-wilding, and de-extinction.